1998
DOI: 10.1107/s090744499701069x
|View full text |Cite
|
Sign up to set email alerts
|

The FNR-like domain of the Escherichia coli sulfite reductase flavoprotein component: crystallization and preliminary X-ray analysis

Abstract: The FNR-like domain of the Escherichia coli sulfite reductase flavoprotein subunit was crystallized using the hanging-drop technique, with PEG 4000 as precipitant. The crystals belong to space group P3112 or enantiomorph, with unit-cell parameters a = b = 171.0, c --152.1 A. A solvent content of 75% was determined by a calibrated tetrachloromethane/toluene gradient which corresponds to three monomers per asymmetric unit. A 3 A, resolution native data set was collected at beamline W32 of LURE, Orsay, France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Re®nement of both RNase Sa3 structures is under way. The high solvent content in crystal form I is not typical for protein crystals; however, similar values have been frequently observed, for example, crystals of oxygenevolving photosystem II with a solvent content of 66% (Shen & Kamiya, 2000), rotavirus protein VP6 with a solvent content of 70% (Petitpas et al, 1998), the complex of tRNAAsp with aspartyl-tRNA synthetase with a solvent content of 75% (Briand et al, 1998), FNR-like domain of the sul®te reductase¯avoprotein subunit with a solvent content of 75% (Gruez et al, 1998), glutathione S-transferase with a solvent content of 75% (Rossjohn et al, 1997) and glucosamine-6-phosphate deaminase with a solvent content of 78% (Horjales et al, 1999).…”
Section: Resultsmentioning
confidence: 55%
“…Re®nement of both RNase Sa3 structures is under way. The high solvent content in crystal form I is not typical for protein crystals; however, similar values have been frequently observed, for example, crystals of oxygenevolving photosystem II with a solvent content of 66% (Shen & Kamiya, 2000), rotavirus protein VP6 with a solvent content of 70% (Petitpas et al, 1998), the complex of tRNAAsp with aspartyl-tRNA synthetase with a solvent content of 75% (Briand et al, 1998), FNR-like domain of the sul®te reductase¯avoprotein subunit with a solvent content of 75% (Gruez et al, 1998), glutathione S-transferase with a solvent content of 75% (Rossjohn et al, 1997) and glucosamine-6-phosphate deaminase with a solvent content of 78% (Horjales et al, 1999).…”
Section: Resultsmentioning
confidence: 55%
“…Previous work has demonstrated that cysK , which encodes an enzyme in L-cysteine biosynthesis, is subject to FNR regulation and identified an FNR-like domain in cysJ, which encodes a component of the sulfite reductase [16, 61]. Here, we found that loss of FNR affects the entire L-cysteine biosynthetic pathway including genes involved in the uptake and transport of sulfate ( i.e.…”
Section: Resultsmentioning
confidence: 61%
“…The crystal structure of SiR‐HP has been solved at 1.6 Å resolution [10] but structural information about SiR‐FP is not available yet despite preliminary results obtained with the isolated FAD‐binding domain [11]. The FMN and FAD cofactors are involved in different diaphorase catalytic activities used for the in‐vitro characterization of the protein [1,3,12,13].…”
mentioning
confidence: 99%